Relationship between diabetes and ischaemic injury among patients with revascularized ST‐elevation myocardial infarction. Issue 12 (25th July 2017) - Reinstadler, Sebastian J.; Stiermaier, Thomas; Eitel, Charlotte; Metzler, Bernhard; de Waha, Suzanne; Fuernau, Georg; Desch, Steffen; Thiele, Holger; Eitel, Ingo
Abstract : Aims: Studies comparing reperfusion efficacy and myocardial damage between diabetic and non‐diabetic patients with ST‐elevation myocardial infarction (STEMI) are scarce and have reported conflicting results. The aim was to investigate the impact of preadmission diabetic status on myocardial salvage and damage as determined by cardiac magnetic resonance (CMR), and to evaluate its prognostic relevance. Materials and Methods: We enrolled 792 patients with STEMI at 8 sites. CMR core laboratory analysis was performed to determine infarct characteristics. Major adverse cardiac events (MACE), defined as a composite of all‐cause death, non‐fatal re‐infarction and new congestive heart failure, were recorded at 12 months. Patients were categorized according to preexisting diabetes mellitus (DM), and according to insulin‐treated DM (ITDM) and non‐insulin‐treated DM (NITDM). Results: One‐hundred and sixty (20%) patients had DM and 74 (9%) were insulin‐treated. There was no difference in the myocardial salvage index, infarct size, microvascular obstruction and left ventricular ejection fraction between all patient groups (all P > .05). Patients with DM were at higher risk of MACE (11% vs 6%, P = .03) than non‐DM patients. After stratification according to preadmission anti‐diabetic therapy, MACE rate was comparable between NITDM and non‐DM ( P > .05), whereas the group of ITDM patients had significantly worse outcome ( P < .001). Conclusions: Diabetic patients with STEMI, especially those having ITDM, had an increased risk of MACE. The adverse clinical outcome was, however, not explained by an impact of DM on reperfusion success or myocardial damage. Clinical trial registry number: NCT00712101.